Windows 10 all-in-one - Leonhard, Woody (--For dummies., 2018)
Are you ready to become the resident Windows 10 expert in your office? Look no further! This book is your one-stop shop for everything related to the latest updates to this popular operating system. With the help of this comprehensive resource, you'll be able to back up your data and ensure the security of your network, use Universal Apps to make your computer work smarter, and personalize your Windows 10 experience. Windows 10 powers more than 400 million devices worldwide--and now you can know how to make it work better for you with Windows 10 All-in-One For Dummies. You'll find out how to personalize Windows, use the universal apps, control your system, secure Windows 10, and so much more.--Amazon.com.